The Effectiveness of Digital-Based Zakat Distribution on the Economic Empowerment of Mustahik: A Sharia Economic Perspective Analysis - Siti Amalika; Abd Hamid (Idarotuna : Journal of Administrative Science, 2026)
This study analyzes the effectiveness of digital-based zakat distribution in empowering the economy of mustahik through an Islamic economic perspective, where the governance transformation from conventional to digital systems is proven to enhance the accuracy, transparency, and speed of productive fund distribution. Utilizing a qualitative narrative-analytical approach through case studies and the Miles and Huberman interactive model analysis, the findings reveal that the implementation of features such as digital scoring, real-time monitoring, and e-wallet integration significantly minimizes mistargeting and accelerates the distribution of business capital. The impact is evident not only in the strengthening of accountability and financial literacy among mustahik but also in the improvement of the economic independence index and the reduction of failure risks for micro-enterprises. Theoretically, the digitalization of zakat represents the actualization of the maqāṣid al-sharīʿah principles, specifically ḥifẓ al-māl (preservation of wealth) and distributive justice. This confirms that institutional ijtihad through this hybrid governance model is highly strategic in realizing inclusive and sustainable Islamic economic development